Utilization of pyrazole-perimidine hybrids bearing different substituents as corrosion inhibitors for 304 stainless steel in acidic media - UĞUZ NELİ, ÖZLEM; KOCA, ATIF (My University, 2022)
© 2022Water soluble Pyrazole-Perimidine (PYR-PER) hybrids bearing various anchoring groups has been synthesized and their corrosion inhibitive efficiencies for the 304 stainless steel in 1.0 M hydrochloric acid has been investigated by the electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PDP), open circuit potential (OCP) measurements, and Density Functional Theory (DFT) B3LYP functional combined with 6-311++G(d,p) basis set. The analyses show that all PYR-PER hybrids effectively reduced the corrosion current density, increased corrosion resistance and inhibited the corrosion of the 304 stainless steel in 1.0 M hydrochloric acid at 298 K. The results indicated that the hybrids functioned as a mixed type inhibitors with anodic suppression outweighing the cathodic one. Multi-functional heteroatoms and methyl, fluoride, chloride, and bromide substituents of pyrazole derivatives considerably enhanced the inhibition efficiencies of the hybrids. The highest corrosion inhibitive efficiency (as 97.45%) was achieved with PYR-PER3 bearing methyl and bromide anchoring groups on the benzene group of the main PYR-PER structure. Some quantum chemical parameters, EHOMO, ELUMO, ΔE, electronegativity, chemical hardness, chemical softness, electrophilicity index, proton affinity and ΔN electron transfer were also discussed. Additionally non-linear optical properties (NLO) were investigated. The results in the B3LYP technique supported by experimental results.
Keywords: Kimya; Fizikokimya; Temel Bilimler; Chemistry; Physical Chemistry; Natural Sciences; KİMYA, FİZİKSEL; Temel Bilimler (SCI); CHEMISTRY, PHYSICAL; CHEMISTRY; Natural Sciences (SCI); Yüzeyler ve Arayüzler; Kimya (çeşitli); Genel Kimya; Fiziksel ve Teorik Kimya; Yüzeyler, Kaplamalar ve Filmler; Fizik Bilimleri; Surfaces and Interfaces; Chemistry (miscellaneous); General Chemistry; Physical and Theoretical Chemistry; Surfaces, Coatings and Films; Physical Sciences; Pyrazole-perimidine hybrids; Corrosion inhibition; Potentiodynamic polarization; Electrochemical impedance spectroscopy; DFT; MILD-STEEL CORROSION; CARBON-STEEL; PYRIMIDINE-DERIVATIVES; ORGANIC-COMPOUNDS; GREEN; RESISTANCE; HCL; ELECTRONEGATIVITY; ALUMINUM; BROMIDE